SWEARWORDS AMONG WOMEN IN BACHELORETTE MOVIE - BAYU A, KUSWIDYANTO (Language Horizon: Journal of Language Studies, 2014)
Kajian ini ditujukan untuk menjelaskan penggunaanswearwordsdalam film Bachelorette. Swearwordspadaumumnyadiucapkanolehkaumpria di masyarakat(Jay, 2000). Namun di masakini, kaumwanita pun cenderungmelakukanSwearwords(Edwards, 2009). Sepertihalnya yang dapatdijumpaipada film Bachelorette yang mayoritastokohwanitanyaseringmengucapkanSwearwords. Berdasarkan Magnus Ljung (2011), ada lima tematentangswearwordsyaituthe religious/ supernatural theme, the scatological theme, the sex organ theme, the sexual activities theme, and the mother (family) theme.Dari film tersebut, penelitianiniakanmencobamenganalisajenis - jenisSwearwords yang diucapkan di konteksdansituasitertentu. Descriptive qualitative adalahmetode yang digunakandalampenelitianini. Pengumpulan data dilakukandenganmengelompokkandanmenganalisa dialog di antarakarakterwanita yang terdapatSwearwordsdalam film Bachelorette. Alat yang digunakanadalahpenelitisendiri yang menggunakan laptop, pemutar video KMP, dan earphone untukmembantupenelitidalammengumpulkandata.HasilpenelitianmenunjukkanbahwaSwearwords di film Bachelorette yang diucapkanoleh para tokohwanitadikelompokkankedalam lima tema. Tema - tematersebutantara lain the religious/ supernatural theme, the scatological theme, the sex organ theme, the sexual activities theme, and the mother (family) theme. Kelimatematersebutteraplikasidalamempatkonteksyakniuntukmengekspresikankemarahan, rasa frustasi, keterkejutanataukejadiantakterduga, danuntukmemberidukungan. Dari hasil yang didapat, fuck cenderungseringdiucapkandanmunculdalamberbagaikonteks di film Bachelorette. Kata kunci:Swearwords, wanita, dan film Bachelorette Abstract This paper is to reveal the use of swearwords in Bachelorette movie. Swearwords are usually uttered by men in society (Jay, 2000). Nowadays, women also tend to do swearing (Edwards, 2009). This can be seen in Bachelorette movie which tends to expose women who produce a lot of swearwords. According to Magnus Ljung (2011), there are five themes of swearwords such as religious/ supernatural theme, the scatological theme, the sex organ theme, the sexual activities theme, and the mother (family) theme(Ljung, 2011).From that movie, this research tries to analyze what types of swearwords which are uttered in particular circumstances. Descriptive qualitative method is used in this research. The data collection was done by gathering and analyzing the dialogs which contain of swearwords among the women characters in Bachelorette movie. The instrument was the researcher himself who uses a laptop, KMP player, and the earphone to help the researcher to collect the data. The findings from the research show that swearwords in Bachelorette movie which are used by women characters are categorized into five themes. They are religious/ supernatural theme, the scatological theme, the sex organ theme, the sexual activities theme, and the mother (family) theme. Those categories are applied in four circumstances such as to express anger feeling, frustration, surprised or unexpected accident, and support giving. From the findings, fuck tend to be uttered in any circumstances in Bachelorette movie. Key words:Swearwords, women, and Bachelorette movie.